Pengalaman Pasien Hipertensi Primer Suku Minang yang Menjalani Perawatan di Rumah : Experiences of Minang Primary Hypertension Patients Undergoing Home Care - Rina; Setiawan; Cholina Trisna Siregar (Fakultas Keperawatan Universitas Andalas, 2016)
Primary hypertension if not controlled properly at home will develop into secondary hypertension which may cause damage to the target organ. Primary hypertension is often called the